A Learning Need Analysis in English Speaking Program for Students of Pondok Tahfidz Al-Qur’an - Karman, Karman; Andas, Netty Huzniati; Ibrahim, Nur Aisah; Suhrah, Suhrah (Journal of English Language and Education, 2024)
This research was aimed to answer the question of research namely What were the learning needs of the students in the English Speaking Program at Pondok Tahfidz Al-Qur’an Al-Hudzaifiyyah? To answer the research question, a survey research was employed. The instruments of the research were questionnaires and interview guidelines. The data were explained in the description form. The participants of the research were 20 students at Pondok Tahfidz Al-Qur’an Al-Hudzaifiyyah Kolaka as the respondents for the questionnaire, and five students were chosen as the respondents for the interview. The result showed that they needed to speak English in religious context, but the problem was that their speaking skills were still weak. Secondly, learning need of the students in learning English were materials that provided vocabularies related to Islamic studies, conversation exercises regarding religious activities, and English grammar which is suitable with their speaking level.